PERBANDINGAN PENDAPATAN USAHATANI KENTANG SELAMA PANDEMI COVID-19 DI KABUPATEN GOWA - Sitti Hardiyanti Mulaputri; Didi Rukmana; Jusni Jusni; Saadah Saadah (Universitas Galuh, 2022)
Currently, Indonesia is facing the pandemic of Covid-19 which had a negative impact on all sectors, including the agricultural sector. One of them is the price of potatoes at the farm level which fluctuates so that it will affect the income of potato farming. This condition is also experienced by potato farmers in Gowa Regency. This study aims to analyze the differences in the income of potato farmers before and during pandemic of Covid-19 in Gowa Regency. This study used T-test analysis using the SPSS program. The results of this study indicate that there is a significant difference between the income of potato farmers before and during the pandemic of Covid-19.